ALIH KODE DAN CAMPUR KODE PADA FILM “UANG PANAI’ (TINJAUAN SOSIOLINGUISTIK): CODE-SWITCHING AND CODE-MIXING IN THE FILM ‘UANG PANAI’ (A SOCIOLINGUISTIC REVIEW) - Puspita Ilham, Siska; Usman; Haliq, Abdul; Wijayanti, Tuti (Journal of Applied Linguistics and Literature, 2023)
This research aims to describe the form and function of code switching and code mixing in the movie Uang Panai'. This research uses descriptive and qualitative methods. Data collection techniques were obtained using the reading and note-taking techniques. Data analysis techniques include identifying, classifying, and describing. The results of research on the speech incident in the film Uang Panai', found that there were speeches that were categorized into code switching and code mixing. The forms of code switching used in the film Uang Panai' include internal code switching and external code switching. The code-switching functions found in each data point in the film Uang Panai' are three: a more persuasive function, a more communicative function, and a more argumentative function. The form of code mixing found in the film Uang Panai' involves mixing internal and external code in the form of words, phrases, and clauses. The code-mixing functions found in each data point in the film Uang Panai' are three: a more persuasive function, a more communicative function, and a more argumentative function.